Предмет: Математика,
автор: лол438
1,4(3-х)-0,9(х+2)=4,7
Ответы
Автор ответа:
0
4,2-1,4x-0,9x-1,8=4,7
2,4-2,3x=4,7
-2,3x=-2,4+4,7
-2,3x=2,3
x=-1
2,4-2,3x=4,7
-2,3x=-2,4+4,7
-2,3x=2,3
x=-1
Автор ответа:
0
1,4(3-х)-0,9(х+2)=4,74,2-1,4х-0,9х-2,8=4,7
-1,4х-0,9х=4,7-2,8-4,2
2,3х=-2,3
х=-1
-1,4х-0,9х=4,7-2,8-4,2
2,3х=-2,3
х=-1
Похожие вопросы
Предмет: Английский язык,
автор: evelinaflaum
Предмет: Геометрия,
автор: Аноним
Предмет: Алгебра,
автор: Hanter213
Предмет: Химия,
автор: Аноним
Предмет: Физика,
автор: llacky